Teaching the Early Modern Period - Conroy, D.; Conroy, D.; Clarke, D.; Clarke, D. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
This innovative project unites leading scholars of English, History and French to examine the challenges of teaching early modern literature, history and culture within higher education. The volume sets out a variety of approaches to teaching the period and aims to revitalize the connection between teaching and research.